Pengaruh Pelatihan, Disiplin Kerja dan Pengembangan Karir Terhadap Kinerja Pegawai Kantor Kementrian Agama Kabupaten Aceh Barat - Hajar, Siti; Farizal, Hendra (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to use a quantitative approach to the phenomena that occur at the West Aceh Regency Ministry of Religion Office. The data method used in this research was a total sampling technique with a sample of 50 Ministry of Religion employees. The data used is primary data and secondary data. The data analysis techniques that will be used are validity test, reliability test, classical assumption test, multiple linear regression analysis test, hypothesis testing using SPSS22 software and coefficient of determination. The results of this test state that the influence of training, work discipline and career development has an influence on the performance of employees at the Ministry of Religion of West Aceh Regency.